Polynomial stability of Timoshenko system with strong damping and strong distributed delay terms (Nonlinear Studies, 2025)
In this research work, we study the linear Timoshenko problem with a strong damping and a strong distributed delay when it acts on the first equation. We first prove the existence and uniqueness of solution of the system by using the semi-group theory. Then, we illustrate the lack of exponential stability even in the condition of equal wave propagation is satisfied. Furthermore, we show the polynomial decay of solution with rate t1/2 . From this perspective, we demonstrate the optimality of the rate